Childhood gastroenteritis: a population study. Issue 6546 (30th August 1986) - Isaacs, D; Day, D; Crook, S
Abstract : A prospective study of gastroenteritis based on a population was carried out for 12 months on over 7000 children in general practice. The incidence of gastroenteritis was highest in the first year (127.7 children affected per 1000) and second year (90.8) of life, and gastroenteritis was rare after six years of age. Children from urban areas had gastroenteritis more commonly than children from semirural areas. A potential pathogen was isolated from half of the specimens: 78% were viruses, and rotavirus was identified most often.